"xy''+y'+ \\frac{\\lambda}{2 }y=0"
We begin by making some assumptions which will simplify the problem. This will turn our differential equation into a constant-coefficient equation.
Let
"t=lnx"
And
"y(x)=\\phi (ln x)=\\phi(t)"
"y'(x)=\\frac{1}{x}(\\frac{d \\phi (t)}{dt})"
"y''(x)=\\frac{1}{x^2}(\\frac{d^2 \\phi (t)}{dt^2}-\\frac{d \\phi (t)}{dt})"
Next, we substitute our new y's to the original equation and simplify until we get a second order, constant coefficient equation.
This is easy to solve with a characteristic equation.
Solving for r we get
"\\sqrt{r^2}=\\sqrt{-\\frac{\\lambda}{2}x} \\implies r=\\sqrt{-\\frac{\\lambda}{2}x}"
We now write out the solution in exponential form.
Converting back to "y(x)" we get
Applying Euler's identities and picking two linear independent solutions
"\\epsilon ^{0} = 1"
Substituting our boundary conditions.
Starting with y'(1) we get
"y(1)=0=C_3sin0+C_4cos0=C_4 \\implies C_4=0"
"y'(\\epsilon ^{2\\pi})=0"
"y'(\\epsilon^{2\\pi})=0=C_3(\\epsilon^{2\\pi})sin(\\sqrt{\\frac{-\\lambda x}{2}ln(\\epsilon^{2\\pi})}"
"n \\pi=\\sqrt{\\frac{-\\lambda x}{2}ln(\\epsilon^{2\\pi})} \\implies \\lambda=(\\frac{2n\\pi}{x \\epsilon^{2\\pi}})^2--->Eigenvalue"
Simplifying to get the eigenfunction, we get
"y(x)=Cx\\sin \\sqrt{x(\\frac{2n\\pi}{2x \\epsilon^{2\\pi}})^2}lnx \\implies y(x)=Cx\\sin \\frac{n\\pi}{x \\epsilon^{2\\pi}}\\sqrt{lnx}--->Eigenfunction"
Comments
Leave a comment